Multi‐Pulse Corona Discharges in Thunderclouds Observed in Optical and Radio Bands. Issue 13 (8th July 2022) - Li, Dongshuai; Luque, Alejandro; Lehtinen, Nikolai G.; Gordillo‐Vázquez, F. J.; Neubert, Torsten; Lu, Gaopeng; Chanrion, Olivier; Zhang, Hongbo; Østgaard, Nikolai; Reglero, Víctor
Abstract: How lightning initiates inside thunderclouds remains a major puzzle of atmospheric electricity. By monitoring optical emissions from thunderstorms, the Atmosphere‐Space Interactions Monitor (ASIM) onboard the International Space Station is providing new clues about lightning initiation by detecting Blue LUminous Events (BLUEs), which are manifestations of electrical corona discharges that sometimes precedes lightning. Here we combine optical and radio observations from a thunderstorm near Malaysia to uncover a new type of event containing multiple optical and radio pulses. We find that the first optical pulse coincides with a strong radio signal in the form of a Narrow Bipolar Event (NBE) but subsequent optical pulses, delayed some milliseconds, have weaker radio signals, possibly because they emanate from a horizontally oriented electrical discharges which does not trigger full‐fledged lightning. Our results cast light on the differences between isolated and lightning‐initiating electrical discharges. Plain Language Summary: One of the biggest mysteries in the atmospheric sciences is to understand how lightning is initiated inside thunderclouds. By combining observations in optical and radio bands, our work uncovers a yet‐unreported type of lightning process: multi‐pulse corona discharges. For the first time, we cast light on the differences between the isolated and lightning‐initiating electrical discharges. Our results indicate that there is an unexpected class of horizontally oriented electrical discharges between those that are fully isolated and those that initiate a leader. They have been ignored by all the radio observations so far due to their weak radio signals. However, this would be the class of electrical discharges that play a significant role in the initiation of the lightning leaders. Key Points: Optical multi‐pulse corona discharges coincide with Narrow Bipolar Events and their subsequent pulses Subsequent optical pulses are related to horizontally oriented electrical discharges which sometimes emit weak radio signals The class of horizontally oriented electrical discharges might play a significant role in the initiation of the lightning leaders